2005
DOI: 10.1530/eje.1.02016
|View full text |Cite
|
Sign up to set email alerts
|

The tumour necrosis factor (TNF)-α system is activated in accordance with pulse pressure in normotensive subjects with type 1 diabetes mellitus

Abstract: Objective: Pulse pressure (PP) and inflammation are important predictors of cardiovascular disease (CVD), even in the normotensive. The age-related increase in PP can be diagnosed up to 20 years earlier in subjects with type 1 diabetes mellitus (T1DM) than in the general population. Some evidence suggests that PP can stimulate inflammation. Our aim was to study the relationship between PP and plasma inflammatory proteins in normotensive subjects with T1DM. Design: This was a cross-sectional study of a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…We also did not find a correlation between adiponectin and TNF-α or IL-6 levels. Although many studies have described a role of TNF-α and IL-6 in insulin resistance, disturbed glucose tolerance and microangiopathy [9,[25][26][27][28][29], we were also unable to show such a relationship in our patients who had developed complications. Similar to our findings, studies have shown that serum leptin levels increase with BMI, female sex, puberty and diabetic nephropathy but do not differ between type I DM patients and healthy controls [16,[30][31][32][33].…”
Section: Discussioncontrasting
confidence: 75%
“…We also did not find a correlation between adiponectin and TNF-α or IL-6 levels. Although many studies have described a role of TNF-α and IL-6 in insulin resistance, disturbed glucose tolerance and microangiopathy [9,[25][26][27][28][29], we were also unable to show such a relationship in our patients who had developed complications. Similar to our findings, studies have shown that serum leptin levels increase with BMI, female sex, puberty and diabetic nephropathy but do not differ between type I DM patients and healthy controls [16,[30][31][32][33].…”
Section: Discussioncontrasting
confidence: 75%
“…In type 1 DM patients, increased PP can be detected early and is associated with CVD (18,19). Recently, one study showed that in type 1 DM patients, the PP level was positively associated with activation of the tumor necrosis factor-␣ system, a marker of systemic inflammation (20). Thus, improvement in PP suggests a potential antiinflammatory role of pancreas transplant and is consistent with the findings of improved endothelial function observed in SPK patients (8).…”
supporting
confidence: 67%
“…Peripheral polyneuropathy was assessed through a previously described two-step protocol combining the 15–item MNSI (Michigan Neuropathy Screening Instrument) questionnaire and a physical examination [28]. Retinopathy was always evaluated by the same ophthalmologist.…”
Section: Methodsmentioning
confidence: 99%